Program Deteksi Dini Penyakit Paru Obstruktif Kronik (PPOK) bagi Lansia di Wilayah Rawan Polusi - Arbaningsih, Sri Rezeki (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2025)
Chronic Obstructive Pulmonary Disease (COPD) is a progressive respiratory condition that significantly affects the elderly, especially in areas with high air pollution. This study aimed to explore the implementation of an early detection program for COPD among elderly residents in pollution-prone areas using a qualitative descriptive approach. Data were collected through in-depth interviews, observations, and document analysis. The results show that the program was generally well-received, with active participation from health workers and community cadres. However, challenges such as limited understanding of COPD, fear of diagnosis, and logistical constraints remain. Positive responses were influenced by effective health education and community support. The study concludes that early detection programs are crucial and should be culturally sensitive, community-based, and integrated with primary health care services to be effective in managing COPD among the elderly in high-risk areas.